Pengaruh Optimalisasi Ekosistem Pembayaran Digital dan Pengendali Inflasi terhadap Pertumbuhan Ekonomi di Indonesia - Anggi Dwi Astuti; Mera Zahara; Adelia Josenia; Shasy Zulia Daufuard; Maya Panorama (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
This study examines the impact of optimizing the digital payment ecosystem and the effectiveness of inflation control on Indonesia’s economic growth. To create a friendly investment climate for national development and maintain purchasing power, it is crucial to maintain or maintain consistent price stability through inflation control. Given the increasingly rapid pace of digital transformation, the cash payment system has reached a critical foundation for increasing transaction efficiency. Using a quantitative approach based on multiple linear regression analysis of secondary data from 2015 to 2025, this analysis shows that optimizing the digital payment ecosystem can be reflected in the volume of digital money transactions (QRIS), which have a significant impact on GDP growth. This, coupled with effective inflation control, can strengthen the effect of optimizing digitalization on national economic stability. The findings of this analysis emphasize the need to strengthen equitable digital infrastructure and cooperation between monetary policy and innovation in financial technology to ensure sustainable economic growth during the era of digital modernization.